Agreement between a body-mounted inertial sensors system and subjective observational analysis when evaluating lameness degree and diagnostic analgesia response in horses with forelimb lameness - Porrakote K. Rungsri (2018)
In 24 horses a lameness was assessed on the straight line before and after diagnostic anaesthesia by a body-mounted inertial sensor systems (BMISS) and by two experience veterinarians. For further studies video clips test unit (n = 101) of all the trials were used. The lameness evaluators were blinded from the results of the BMISS. The inter-observers agreement and agreement of lameness evaluation between BMISS and observers were classified into 3 categories; 1) right forelimb lameness or right forelimb lameness greater than left forelimb lameness, 2) left forelimb lameness or left forelimb lameness greater than right forelimb lameness, and 3) sound or equal right and left forelimb lameness. Kappa statistic (κ), percentage of inter-observers agreement and between BMISS and subjective system (examiners opinion) are reported. The response of anaesthesia agreement was determined by 6 categories between body-mounted inertial sensors system and high experienced observers. This data were analyzed by calculation of the Kendall' tau (b) test. Inter-observer agreement was almost perfect in the clinicians group who assessed the horses in live clinical situation; moderate in the high and in the moderate experienced group and fair in the interns group in video without sound assessment for 85% (κ= 0.89), 73% (κ = 0.53), 69% (κ = 0.44) and 61 % (κ = 29) respectively. The detection agreement between objective (BMISS) and subjective assessment was highest for experienced observers in live clinical situation 79% (κ = 0.58). In video assessment this agreement was moderate for experienced, 74% (κ = 0.52), and moderate experienced veterinarians 70% (κ= 0.48) but fair for the group of interns 67% (κ = 0.40). The average agreement of lameness improvement after anaesthesia between a BMISS and high experienced observers was moderate [T b Value = 0.291]. In conclusion, this study supported that the visual lameness detection depends on the experience of the observer. Results of lameness evaluation of horses with a BMISS and subjective lameness evaluation had moderate agreement of lameness detection and had moderate agreement of lameness improvement after anaesthesia even in experienced observers. This system is a practical and useful tool for the objective lameness detection and can help to prove the effects of regional or joint anaesthesia in horses in clinical situation.